Learning Styles of Vietnamese Medical Students - Thanh Nhan, Vo (Canadian Medical Education Journal, 2010)
Background: The purpose of this study was to assess the learning styles of Vietnamese medical students at the Ho Chi Minh City University of Medicine and Pharmacy. Method: Participants were 856 (147 first-year, 144 second-year, 144 third-year, 136 fourth-year, 148 fifth-year, and 137 sixth-year students) medical students who completed the 100-item Vermunt’s Inventory of Learning Styles. Results: Factor analysis resulted in four factors with adequate reliability (α range: 0.71 - 0.86): Meaning-directed learning style (factor 1), passive, undirected learning style (factor 2), application-directed learning style (factor 3), and reproduction-directed learning style (factor 4). Final-year students employed more deep processing, concrete processing, self regulation, use of knowledge, but more stepwise processing, certification orientation, intake of knowledge than did the freshmen. Students with higher achievement classifications had higher mean score of deep processing, concrete processing, self-regulation, construction of knowledge, and use of knowledge, lower certificate and ambivalent orientation. Discussion: Four theoretically meaningful and cohesive factors underlying learning patterns emerged from the factor analysis. The learning styles of Vietnamese medical students were relatively similar to Asian students, but there were some differences from European students. Conclusion: The assessment of learning styles of medical students may help curriculum renewal, the application of teaching and assessment methods, and improve student learning.